Maternal nano-titanium dioxide inhalation alters fetoplacental outcomes in a sexually dimorphic manner - Griffith, Julie A.; Dunn, Allison; DeVallance, Evan; Schafner, Kallie J.; Engles, Kevin J.; Batchelor, Thomas P.; Goldsmith, William T.; Wix, Kimberley; Hussain, Salik; Bowdridge, Elizabeth C.; Nurkiewicz, Timothy R. (Frontiers in Toxicology, 2023)
The placenta plays a critical role in nutrient-waste exchange between the maternal and fetal circulations, thus functioning as an interface that profoundly impacts fetal growth and development. The placenta has long been considered an asexual organ, but, due to its embryonic origin it shares the same sex as the fetus. Exposures to toxicant such as diesel exhaust, have been shown to result in sexually dimorphic outcomes like decreased placental mass in exposed females. Therefore, we hypothesize that maternal nano-TiO2 inhalation exposure during gestation alters placental hemodynamics in a sexually dimorphic manner. Pregnant Sprague-Dawley rats were exposed from gestational day 10–19 to nano-TiO2 aerosols (12.17 ± 1.69 mg/m3) or filtered air (sham-control). Dams were euthanized on GD20, and fetal tissue was collected based on fetal sex: whole placentas, placental junctional zone (JZ), and placental labyrinth zone (LZ). Fetal mass, placental mass, and placental zone percent areas were assessed for sex-based differences. Exposed fetal females were significantly smaller compared to their exposed male counterparts (2.65 ± 0.03 g vs 2.78 ± 0.04 g). Nano-TiO2 exposed fetal females had a significantly decreased percent junctional zone area compared to the sham-control females (24.37 ± 1.30% vs 30.39 ± 1.54%). The percent labyrinth zone area was significantly increased for nano-TiO2 females compared to sham-control females (75.63 ± 1.30% vs 69.61 ± 1.54%). Placental flow and hemodynamics were assessed with a variety of vasoactive substances. It was found that nano-TiO2 exposed fetal females only had a significant decrease in outflow pressure in the presence of the thromboxane (TXA2) mimetic, U46619, compared to sham-control fetal females (3.97 ± 1.30 mm Hg vs 9.10 ± 1.07 mm Hg) and nano-TiO2 fetal males (9.96 ± 0.66 mm Hg). Maternal nano-TiO2 inhalation exposure has a greater effect on fetal female mass, placental zone mass and area, and adversely impacts placental vasoreactivity. This may influence the female growth and development later in life, future studies need to further study the impact of maternal nano-TiO2 inhalation exposure on zone specific mechanisms.